Genetic analysis of body conformation traits of indigenous Uttara chicken - MK Singh; S Kumar; RK Sharma; SK Singh; B Singh; DV Singh (Journal of Livestock Biodiversity, 2025)
This investigation aimed to evaluate genetics of body conformation characteristics in indigenous of Uttara chicken maintained at Govind Ballabh Pant University of Agriculture and Technology (India). Data was analysed using leastsquares analysis of variance technique. Least squares means of shank length, keel length and breast angle were estimated at 8 and 20 weeks of age. Sires of the chicks signi icantly (p